Platelet Cryopreservation. 1. Development of Cryopreservative Solutions, Based on Cryoprotectant Combination and Study of Their Efficiency - Bogdanchikova, O. A.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2009)
Cryoprotective efficiency of cryopreservative solutions, based on combining different cryoprotectants during platelet freezing, was studied in the research. There were established the cryoprotectant combinations such as: 10% dimethyl acetamide (DMAC)/1,2-propane diol (1,2-PD), DMAC/glycerol and DMAC/oxyethylated glycerol (n = 5), significantly increasing the integrity of cryopreserved platelets, compared to the results of freezing under protection of monocryoprotective media, containing one of the mentioned above substances, including 10% dimethyl sulfoxide.